(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article analyzes the theoretical principles of the problem of self-actualization and psychological well-being of the individual. The main characteristics of these phenomena are described and the features of their connection are investigated. The main components of self-actualization are considered, as tendencies to realization of internal potential and development of own abilities. The structure and features of the formation of psychological well-being of a person are determined. It is revealed that psychological well-being, reflecting the internal state of the individual, is a criterion for how an individual is satisfied with himself and his life and serves as an indicator of a person’s orientation towards self-actualization.